External Debt, Export and Growth in Asian Countries: 1988-2006 - Lau, Evan; Kon, Thian Ling (Asian Network for Scientific Information, 2014)
Utilizing panel data investigation, this study examines the nexus between external debt and economic growth, covering seventeen Asian countries. The study found that external debt works through two channels: Directly, in which the causality runs from external debt to GDP and indirectly, in which it positively enhances exports through GDP. This opens another channel through which foreign financial capital can potentially stimulate exports through economic growth while strengthening the bidirectional causality between exports and GDP. With the backdrop of uncertainties around the globe, e.g., the debt crisis, efficient coordination and cooperation in implementation of debt management to support economic development should be on every Asian regional agenda.